Choosing or Inheriting the Joneses: The Origins of Reference Groups - Martín Leites; Camila Paleo; Xavier Ramos Morilla; Gonzalo Salas (Institute of Labor Economics (IZA), 2022)
Do individuals choose their reference groups, i.e. their Joneses, or are they culturally transmitted across generations? We provide evidence that feeds the theoretical debate about the endogeneity or exogeneity of reference groups. Our findings for Uruguay suggest that reference groups are largely transmitted across generations. We also find individuals to have multiple reference groups and these to be context-specific. Our results are robust to several checks and to endogeneity issues.
Keywords: D31; D62; D63; Z13; 330; intergenerational transmission; reference group; income comparisons